A Survey on Interlinking in Linked Open Data - SA, Shweta; Rao, Shreyas Suresh (International Journal of Computer Sciences and Engineering, 2025)
Semantic Web interconnects diverse data sources on the Web, thereby presenting a global database of Web resources. Interlinking is an important activity in establishing semantic links between applications on the World Wide Web. During the interlinking activity, first, link discovery is done to identify the datasets to be linked, and subsequently, link generation is done to generate the matching links, based on appropriate comparator algorithms. The paper presents a literature review on linked open data, focusing on the interlinking activity. Furthermore, the paper presents a novel map-reduce based approach for comprehensively presenting the interlinking algorithms. Lastly, the paper throws some insights on the LOD datasets available in the LOD Cloud 2018.